The effects of absence of stereopsis on performance of a simulated surgical task in two-dimensional and three-dimensional viewing conditions. Issue 2 (3rd September 2014) - Bloch, Edward; Uddin, Nabil; Gannon, Laura; Rantell, Khadija; Jain, Saurabh
Abstract : Background: Stereopsis is believed to be advantageous for surgical tasks that require precise hand-eye coordination. We investigated the effects of short-term and long-term absence of stereopsis on motor task performance in three-dimensional (3D) and two-dimensional (2D) viewing conditions. Methods: 30 participants with normal stereopsis and 15 participants with absent stereopsis performed a simulated surgical task both in free space under direct vision (3D) and via a monitor (2D), with both eyes open and one eye covered in each condition. Results: The stereo-normal group scored higher, on average, than the stereo-absent group with both eyes open under direct vision (p<0.001). Both groups performed comparably in monocular and binocular monitor viewing conditions (p=0.579). Conclusions: High-grade stereopsis confers an advantage when performing a fine motor task under direct vision. However, stereopsis does not appear advantageous to task performance under 2D viewing conditions, such as in video-assisted surgery.